Libri prohibiti - Svoljšak, Sonja (2019)
In all periods individuals and communities who shared  in the written word their knowledge and findings, views, ideas and visions with others met with forces that wanted to control, direct and limit the flow of knowledge and ideas: they ordered such texts to be rewritten, they confiscated and burned unwanted works, and, in the most extreme cases, their authors were condemned, exiled or even executed. But just as the Earth revolves around the Sun, readers too, have always found their ways to books despite of various strict censorship policies and lists of banned literature. The collection presents selected works kept in the National and University Library, which were once included in the papal index of banned books, or in others, mainly imperial censorship lists.The works were on display at the exhibition entitled And Yet they Were Read - Banned Books in the Early Modern Age; as part of a research project in 2018, it was prepared by the Research Centre of the Slovenian Academy of Sciences and Arts (ZRC SAZU) and NUK.https://www.dlib.si/razstave/libri-prohibiti/
The collection presents selected works from the National and University Library's collection, which were in the past marked as religiously, morally or politically controversial and listed on the Papal Index and other, mainly imperial censorship lists. The works were displayed at the exhibition And Yet They Read Them – Banned Books in the Early Modern Age. It was part of the Banned Books on Slovenian Territory in the Early Modern Age research project, and was prepared in 2018 by the Research Centre of the Slovenian Academy of Sciences and Arts, and NUL.The virtual exhibition is available at:  https://www.dlib.si/razstave/libri-prohibiti/